Comparison of Bipolar Diathermy with Thunder-beat Device in Surgical Outcome of Tonsillectomy - Bikash Lal Shrestha, Ashish Dhakal, Sammer Karmacharya, Pradeep Rajbhandari, Bikash Lal Shrestha, Ashish Dhakal, Sammer Karmacharya, Pradeep Rajbhandari (Journal of Rawalpindi Medical College, 2019)
Background:. To compare the thunder-beat device with bipolar diathermy in surgical outcome of tonsillectomy. Methods: In this prospective study 75 patients who underwent tonsillectomy on one side using thunder beat device and on the other side using bipolar diathermy, were included . The intra- operative blood loss, operative time, post-operative pain and post-operative haemorrhage were taken for analysis in both the surgical procedures. Results: Among the seventy five patients, the age groups ranged from 19-36 years with mean age 25.36+/-5.54 years. Out of 75 patients, 21 were male and 54 were female.The comparison of operation time and intra-operative blood loss between thunder- beat and bipolar diathermy showed statistically significant differences. The comparison of pain score showed statistically significant result with better pain results in bipolar diathermy whereas the secondary haemorrhage was common in thunder beat device. Conclusion: The thunder-beat use in tonsillectomies is less time consuming with decreased intra-operative blood loss. But, the post- operative pain is more as compared to bipolar diathermy. Though, it is safe and effective in performing tonsillectomy but its cost is the main drawback for its regular use.